Effect of Share Ownership Concentration, Audit Committee Meeting Frequency, Type of External Auditor, and Risk Monitoring Committee Size on Operational Risk Disclosure in Non-Bank Financial Services Institutions (LJKNB) for the 2019-2023 Period - Naomi, Jane; Akbar, Lolita; Galuh Savitri, Ardila; Syamsi, Rachmi; Hanggraeni, Dewi (Jurnal Pendidikan Indonesia, 2025)
In an increasingly complex global business environment, effective corporate governance is one of the main pillars to maintain economic stability and encourage sustainable growth in the financial sector. This study aims to analyze the Effect of Share Ownership Concentration, Audit Committee Meeting Frequency, Type of External Auditor, and Risk Monitoring Committee Size on Operational Risk Disclosure in Non-Bank Financial Services Institutions (LJKNB) for the 2019–2023 Period. The content analysis method was used to collect operational risk disclosure data from the annual reports of 42 LJKNB listed on the IDX during the period 2019 to 2023. Using GLS regression analysis, this study shows the influence of governance on the disclosure of operational risks quantitatively and qualitatively. The results show that the concentration of share ownership, the number of audit committee meetings, and the external auditors of the Big 4 have a significant positive effect on the disclosure of quantitative operational risks, while the number of risk monitoring committees has a significant negative effect. The four governance variables did not have a significant effect on the qualitative disclosure of operational risks